A novel conceptual framework of Health Information Systems (HIS) sustainability - Mohamadali, Noor Azizah; Ab Aziz, Nur Faizah; Mohd Zahari, Nurul Aqilah (Institute of Electrical and Electronics Engineers, Inc., 2017)
Sustainable technology means technology is capable of being maintained over a long span of time; independent of shifts in both hardware and software. Effective implementation and use of Health Information Systems (HIS) for years to come are crucial as sustainable HIS. Numbers of studies have discussed various factors contributes towards barriers for successful implementation of HIS. However, very few studies discussed factors on HIS sustainability. Through critical analysis of existing literature on success, failure, and challenges of HIS adoption, this paper identifies four crucial factors that shape the sustainable HIS. The importance of strong leadership support, proper contingency planning, and practice, continuous vendor support, and protection of security and privacy issues are identified by classifying all the factors within these four constructs, and with it, we argue these factors crucial for sustainable HIS. This paper proposes a novel conceptual framework which incorporated all these constructs as HIS sustainability factors. This paper also described the theoretical basics behind the development of the model and methodology to be employed to validate the proposed model.